2017
DOI: 10.1097/md.0000000000008103
|View full text |Cite
|
Sign up to set email alerts
|

Adductor canal block with local infiltrative analgesia compared with local infiltrate analgesia for pain control after total knee arthroplasty

Abstract: Background:This meta-analysis aimed to evaluate the efficiency and safety of the combined adductor canal block with peri-articular infiltration versus periarticular infiltration alone for pain control after total knee arthroplasty (TKA).Methods:PubMed, Medline, Embase, Web of Science, and the Cochrane Library were searched to identify articles comparing the combined adductor canal block with peri-articular infiltration and periarticular infiltration alone for pain control after TKA. Main outcomes were numeric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…However, Li et al [17] demonstrated that ACB preserved greater quadriceps strength more than FNB with similar pain control. Likewise again, the VAS pain scores were relatively lower in the two groups compared with baseline, no significant difference was observed in pain relief at any followup time between the groups, suggesting both ACB and FNB provided better analgesia without any statistical significance in the last meta analyze [18].…”
Section: Discussionmentioning
confidence: 94%
“…However, Li et al [17] demonstrated that ACB preserved greater quadriceps strength more than FNB with similar pain control. Likewise again, the VAS pain scores were relatively lower in the two groups compared with baseline, no significant difference was observed in pain relief at any followup time between the groups, suggesting both ACB and FNB provided better analgesia without any statistical significance in the last meta analyze [18].…”
Section: Discussionmentioning
confidence: 94%
“…However, still there is a lack of clinical trials of the combined adductor canal block with periarticular infiltration versus periarticular infiltration alone for pain management after TKR. There is a study [5] indicated that the combined adductor canal block with periarticular infiltration could significantly reduce VAS scores at rest when compared with periarticular infiltration alone for pain management after TKR.…”
Section: Discussionmentioning
confidence: 99%
“…LAI usually administrates as periarticular or with intra-articular infiltration. Meanwhile, the efficacy of LAI was comparable to that of epidural anesthesia, femoral nerve block (FNB) [2], adductor canal block (ACB) [5], and intrathecal morphine [6]. Sciatic nerve block (SNB) and LAI are two major options to supplement FNB in relieving of pain after TKR, However, its short duration of action limited its clinical application [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations